2022
DOI: 10.3390/molecules27144651
|View full text |Cite
|
Sign up to set email alerts
|

Succinimido–Ferrocidiphenol Complexed with Cyclodextrins Inhibits Glioblastoma Tumor Growth In Vitro and In Vivo without Noticeable Adverse Toxicity

Abstract: SuccFerr (N-[4-ferrocenyl,5-5-bis (4-hydroxyphenyl)-pent-4-enyl]-succinimide) has remarkable antiproliferative effects in vitro, attributed to the formation of a stabilized quinone methide. The present article reports in vivo results for a possible preclinical study. SuccFerr is lipophilic and insoluble in water, so the development of a formulation to obviate this inconvenience was necessary. This was achieved by complexation with randomly methylated cyclodextrins (RAMEßCDs). This supramolecular water-soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Moreover, no difference in IC 50 was observed when different ferrocifens were free or encapsulated in LNCs, confirming results from the literature that LNCs did not alter the ferrocifen efficacy. ,, Moreover, it was possible to distinguish two slopes on cell viability depending on the ferrocifen concentration. This could be associated with a senescence mechanism at low concentrations, as already described for P722 , and also for the ansa-ferrocifen DP1 , followed by an apoptotic mechanism at higher concentrations . Finally, chemical modification performed on the initial P722 did not significantly hamper its efficiency.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Moreover, no difference in IC 50 was observed when different ferrocifens were free or encapsulated in LNCs, confirming results from the literature that LNCs did not alter the ferrocifen efficacy. ,, Moreover, it was possible to distinguish two slopes on cell viability depending on the ferrocifen concentration. This could be associated with a senescence mechanism at low concentrations, as already described for P722 , and also for the ansa-ferrocifen DP1 , followed by an apoptotic mechanism at higher concentrations . Finally, chemical modification performed on the initial P722 did not significantly hamper its efficiency.…”
Section: Resultssupporting
confidence: 60%
“…All studies previously performed on ferrocifen–LNCs showed only the formation of a suspension, compatible with an intravenous administration route, with promising results on several cancers. ,,, For the P769 –LNC gel, the use as a local therapy to treat glioblastoma after tumor resection could be imagined as ferrocifens have already shown efficacy against this cancer. Indeed, Vessières et al showed a large heterogeneity of response to P722 on patient-derived cell-line glioblastoma depending on transcriptomic subtypes . A more recent study also highlighted the efficiency of P722 complexed with cyclodextrins on glioblastomas . Moreover, P769 was tested on the U87MG glioblastoma cell line, with or without LNCs, and the IC 50 values obtained were 67 and 46 nM, respectively, close to the 27 nM obtained with P722 alone, after 96 h of treatment .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SuccFerr was recently formulated with various nanocapsules in its diphenol form, or to increase its lipophilicity and the load in lipid nanocapsules, as monoacetate [22] or diacetate [22][23][24], with or without the unexpected formation of a gel [22]. It was recently formulated with randomly methylated cyclodextrins (RAMEβCDs) and tested in vivo without noticeable adverse toxicity [25], but this last complexation has yet to be analyzed more finely by modelling and laboratory experiments.…”
Section: Ferrociphenol Succferrmentioning
confidence: 99%